The fun and quirky world of online shopping / Efina Hamdan and Maizura Manshor - Hamdan, Efina; Manshor, Maizura (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Welcome to the wild world of online shopping! It is like the Wild West out there, but with more emojis and fewer cowboys. If you have ever found yourself scrolling through your favourite e-commerce site at 3.00 a.m, you are not alone. Let us dive into what makes online shopping so irresistible. First up, let us talk about trends. Have you noticed how shopping on your phone has become as common as texting? Mobile commerce is all the rage because who wants to drag out a laptop when you can shop from yourcozy spot on the couch? Apps and mobile friendly sites make it super easy to buy that cute skirt or the latest gadget with just a few taps. And social media? It is like the new mall. Instagram, Facebook, TikTok – they are not just for memes and catching up with friends. They are full of tempting products waiting to be discovered. Ever bought something because an influencer swore it was life-changing? Yeah, us too.